Understanding the problem. - Neville-Neil, George (New York ACM, 2006)
A koder with attitude, KV answers your questions. Miss Manners he ain't.
Keywords: Software; Programming languages; Language classifications; Java; Software; Programming languages; Language classifications; C; Languages